The punisher (2016), volume 2 ebook End of the line. - Cloonan, Beck (The Punisher (2016), 2017)
Collects The Punisher #7-12. You can't keep Frank Castle buried for long. And the Punisher's mission to bring down a super-powered drug ring is about to reach new heights. As his quest sends him deep into the woods of the Northeast, it's time for Frank to go off-road. But as he gets deeper into the wilderness, has the predator finally become the prey? Agent Ortiz chased Frank into hell and came out the other side. Now she's out for revenge! And while Frank gets help from an unlikely source, trouble's not far behind! If you go out in the woods today, you're sure for a big surprise...